Pendampingan Komunitas Sekolah melalui Kegiatan Vertical Garden untuk Mewujudkan Sekolah Dasar berbasis Lingkungan di SDN 34 Kota Ternate Maluku Utara - Abdul Rasyid Tolangara; Rohima Wahyu Ningrum (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
School yard is the most appropriate learning media to support learning creativity for learners. The narrow use of school yard has not been well implemented, so that the students' ignorance towards the environment is closely related to the decreasing environmental quality in schools. To improve the quality of education and learning achievement of learners about environmental knowledge, school can provide a direct understanding to learners about the environment by applying the concept of vertical garden in the yard of the school. Vertical concept of this garden becomes an alternative way in getting around the yard or narrow land. The school plays an important role in this devotion program at the time of making the garden vertical garden, where the school proposes the implementation of maintenance activities and planting new plant species in the annual plan of SDN 34 Kota Ternate. Socialization and workshops that have been done with the school together with community service team, it can provide an early description of the use of a narrow school yard by applying the garden vertical garden. Another target of this program is that students and teachers feel the benefits of this school park in classroom learning, so that they can apply the concept of farming obtained for the home.